Marketing Strategy Proposal for Mitra Balita Sejahtera as a Means to Compete in the Mom & Baby Industry - Muhammad Fauzi Ramadhan P (Eduvest - Journal of Universal Studies, 2026)
This study proposes a comprehensive marketing strategy for Mitra Balita Sejahtera (MBS) to strengthen competitiveness in the fast-growing mom and baby industry. As digital transformation accelerates and customer expectations shift, MBS faces challenges related to declining online sales, increasing competition, and changing consumer behavior. Using a mixed-methods approach, the research integrates quantitative survey data and qualitative secondary data to analyze both internal capabilities and external market dynamics. Internal analysis through STP, Marketing Mix 7Ps, and VRIO reveals strengths such as a curated product assortment and strong offline credibility, alongside weaknesses in digital marketing capability, operational systems, and reliance on a single marketplace. External assessment using PESTEL and Porter’s Five Forces highlights opportunities driven by e-commerce growth, digital adoption, and supportive SME policies, but also threats from intense price competition, platform dependency, and rapidly shifting consumer trends. These insights are synthesized using SWOT and further developed into a TOWS matrix to formulate strategic alternatives. The proposed strategy emphasizes diversifying sales channels, enhancing digital marketing through social media and influencer collaboration, improving customer experience via better inventory and service quality, and leveraging partnerships to build long-term competitiveness. The study concludes that MBS must adopt an integrated, adaptive, and data-driven marketing strategy to sustain performance in a dynamic environment while continuously developing capabilities for future growth.